PENGARUH DISIPLIN KERJA DAN INSENTIF TERHADAP PRODUKTIVITAS KARYAWAN PANEN PT. GUNUNG MAS RAYA ESTATE KABUPATEN ROKAN HILIR - Masita Hasbia; Pramadewi Arwinence; Tarigan prillina Mida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to find the effect of work discipline and incentives onharvester productivity of PT. Gunung Mas Raya Estate Rokan Hilir Regency. Thepopulation of the study was harvest employees of PT. Gunung Mas Raya EstateRokan Hilir Regency for a total of 218 people, with the number of samples in thisstudy being 69 respondents. The source of the date used is primary data: it iscollected using a aquestionnaire as an instrument to prove the result of the study.In testing the hypothesis of the study, it uses multiple linear regression analysisthrough SPSS program. The sampling technique that has been selected is thepurposive sampling method.The result of the study shows that: 1) there is apositive and significant effect of work discipline on the productivity of employeesof PT. Gunung Mas Raya Estate Rokan Hilir Regency, 2) there is a positive andsignificant effect of providing incentives on the productivity of PT. Gunung MasRaya Estate Rokan Hilir Regency, 3) there is a positive and significant effect ofwork discipline and the provision of incentives simultaneously on the productivityof PT. Gunung Mas Raya Estate Rokan Hilir Regency. Keywords: work discipline, incentives, productivity.